MANAGING POST-BASIC EDUCATION AND CAREER DEVELOPMENT (PBECD) AMIDST ECONOMIC HARDSHIP AND INSECURITY CHALLENGES IN NIGERIA - Ukozor, Conrad Ugochukwu (Multi-Disciplinary Research and Development Journals Int’l, 2025)
The paper discussed strategies to manage Post-Basic Education and Career Development (PBECD) Amidst Economic Hardship and Insecurity Challenges in Nigeria. The paper disclosed that strengthening government funding and resource diversification, enhancing public-private partnerships (ppps) and community participation, improving security and safety management systems, capacity building and motivation of teachers, integrating technology and digital learning platforms, innovating the curriculum and promoting skills-based education, and strengthening policy implementation and monitoring mechanisms are strategies to adopt to effectively manage Post-Basic Education and Career Development (PBECD) Amidst Economic Hardship and Insecurity Challenges in Nigeria. Based on the findings, the paper recommends that the Nigerian government should significantly raise its budgetary allocation to education, particularly at the post-basic level, to meet the UNESCO benchmark of 15–20% of total national expenditure. Educational management should adopt a collaborative model in which the government, the private sector, and communities work together to fund, manage, and secure post-basic education centres. The private sector can contribute through Corporate Social Responsibility (CSR) initiatives, scholarships, and infrastructural support, while communities can assist in safeguarding school environments and monitoring teacher attendance. Industries and vocational institutions should also collaborate to design career development programmes aligned with market demands. This synergy ensures that education remains relevant, practical, and sustainable amidst economic and security difficulties. Teachers and administrators are the key drivers of post-basic education, and their capacity must be developed through continuous professional training, digital skill development, and workshops on modern pedagogy. Digital transformation is a key strategy for sustaining post-basic education during crises. The government should invest in affordable broadband internet, electricity supply, and digital tools to promote e-learning. Schools should be equipped with computer laboratories, and teachers should be trained in digital pedagogy to facilitate hybrid learning models that combine online and in-person instruction.